Implementasi Sistem Informasi Elektronik Pelayanan Ekspor-Impor Sementara Kendaraan Bermotor melalui Modul VHD pada Kantor Bea Cukai Atambua - Yevika Mariany Adoe; Ajis S. Adang Djaha; Masamah Masamah (Journal of Management and Creative Business, 2026)
This study aims to analyze the implementation of the Electronic-Based Temporary Export-Import Service Information System Program (VHD Module) at the Customs and Excise Intermediate Type B Atambua Supervision and Service Office. The research approach uses descriptive qualitative methods through interviews, observations, and document analysis. The results of the study show that the success of program implementation is greatly influenced by effective communication between agencies, the competence of trained human resources, and the positive disposition of employees in carrying out their duties. A proactive and collaborative attitude has proven to be an important factor in creating a work environment that is responsive to system changes. In addition, people as users of the VHD Module application feel an increase in satisfaction after socialization and training that makes it easier to adapt to the new system. These findings affirm the importance of the involvement of all parties, both internal and external, in supporting the implementation process so that program objectives can be achieved optimally. This research provides practical contributions for related agencies in strengthening communication strategies, increasing employee capacity, and expanding community participation to realize more efficient, transparent, and responsive export-import services to user needs.